Development of phenotypic markers and contrast genotype candidates of target minerals related to cassava - Sylvia Nosya Pratama; Sudarsono SUDARSONO; Sintho Wahyuning Ardie; NURUL KHUMAIDA; Dewi Sukma (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Pratama SN, Sudarsono, Ardie W, Khumaida N, Sukma D. 2021. Development of phenotypic markers and contrast genotype candidates of target minerals related to cassava. Biodiversitas 22: 3049- 3056. Cassava leaves have various macro and micro-nutrients with varying levels, such as magnesium, iron, and zinc. The differences in genotypes of cassava may result in different mineral content in cassava leaves. This study aims to determine the estimator phenotypic markers and contrast genotype candidate selection related to target minerals. This study used a one-factor treatment composed of 12 cassava genotypes and arranged in a randomized block design (RBD) which each treatment was repeated 3 times. The observation was conducted on the leaves' qualitative and quantitative characters such as plant growth, leaf morphology, and leaf mineral content characters. The observation was performed at 3 and 6 months after planting. The results showed that the quantitative and qualitative characters that could be used as estimator for mineral content in cassava leaves are the Soil Plant Analysis Development (SPAD)- Chlorophyll value and leaf color. Genotypes G6-1-15-4-3, G6-2-15-1-1, G6-2-15-3-3 (lowest) and Malang (G4D0), G4D1-222, G3D2-413 (highest) could be categorized as contrast genotypes based on SPAD-value and mineral content. The strong positive correlation between Mg and Fe content with SPAD suggested that SPAD is a possible marker for high Mg and Fe content in leaves. Adversely, a weak relationship between SPAD and Zn content in leaves showed that SPAD is a weak marker for Zn content in leaves. Further research related to molecular markers development can be carried out based on these results.